2007
DOI: 10.1139/o07-014
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species and mitochondrial membrane potential are modulated during CDDP-induced apoptosis in EC-109 cellsThis paper is one of a selection of papers in this Special Issue, entitled International Symposium on Recent Advances in Molecular, Clinical, and Social Medicine, and has undergone the Journal's usual peer-review process.

Abstract: cis-Diamminedichloroplatinum (CDDP), commonly know as cisplatin, is a well known DNA-damaging agent, which is highly active in suppressing the proliferation of tumor cells. However, it is not clear that CDDP can induce growth inhibition of esophagus cancer cells. Using the cell line EC-109 from the esophagus, we found that CDDP would induce apoptotic responses. The addition of CDDP to cells led to the inhibition of growth in a time- and dose-dependent manner. CDDP generated reactive oxygen species (ROSs) in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…However, excessive ROS could trigger apoptosis by altering the MMP and damaging the respiratory chain. 20 , 21 Our data demonstrated that TRIM32 had a protective role in cisplatin-induced ROS formation. To our knowledge, this is the first study to show the protective roles of TRIM32 on MMP and ROS in cisplatin-treated NSCLC cells.…”
Section: Discussionmentioning
confidence: 52%
“…However, excessive ROS could trigger apoptosis by altering the MMP and damaging the respiratory chain. 20 , 21 Our data demonstrated that TRIM32 had a protective role in cisplatin-induced ROS formation. To our knowledge, this is the first study to show the protective roles of TRIM32 on MMP and ROS in cisplatin-treated NSCLC cells.…”
Section: Discussionmentioning
confidence: 52%
“…Many classes of DNA-damaging agents are known to induce oxidative stress, 13, 21, 22 which is a major cause for dysfunction of cellular organelles and cell death. 14, 23 Exposure of U1810 cells to bleomycin, cisplatin or TFP alone resulted in moderate increases of intracellular ROS (Figures 7a and b).…”
Section: Resultsmentioning
confidence: 99%
“…However, excessive ROS triggers apoptosis pathway by altering the MMP and damaging the respiratory chain. 17 , 18 Our data demonstrated that Rab18 had a protective role during CDDP-induced ROS formation. Considering the connection between ROS and MMP, it is possible that Rab18 inhibits CDDP-induced ROS production, which maintains MMP and reduces cytochrome c release, thus inhibiting CDDP-induced apoptosis.…”
Section: Discussionmentioning
confidence: 51%